2017
DOI: 10.4081/ijfs.2017.6886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic usage in swine reproduction farms in Umbria region based on the quantitative analysis of antimicrobial consumption

Abstract: Antibiotic use in food-producing animals has considerable impact on public health, especially with respect to the development and spread of antibiotic resistance. Pigs represent one of the main species in which antibiotics are frequently used for different purposes. Surveillance of antibiotic consumption and dose appropriateness, through novel approaches based on defined daily doses, is strongly needed to assess farms’ antibiotic risk, in terms of spread of antibiotic resistance and possibile presence of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Two studies reported partial data (AMU in feeds only) [ 55 , 62 ]. Of the remaining 15 studies, eight reported ‘overall’ AMU on farms [ 45 , 47 , 50 , 51 , 54 , 61 , 67 , 116 ], whereas 7 reported AMU for specific age groups (sows, fattening pigs, suckling pigs, etc.) [ 32 , 46 , 49 , 56 , 57 , 66 , 68 , 117 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported partial data (AMU in feeds only) [ 55 , 62 ]. Of the remaining 15 studies, eight reported ‘overall’ AMU on farms [ 45 , 47 , 50 , 51 , 54 , 61 , 67 , 116 ], whereas 7 reported AMU for specific age groups (sows, fattening pigs, suckling pigs, etc.) [ 32 , 46 , 49 , 56 , 57 , 66 , 68 , 117 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such studies may also shed insights into treatment practices for different diseases or types of animal [ 46 , 83 ]. Finally, they may also allow to identify production types, farm sizes, and animal groups at higher risk of usage [ 45 , 116 ], as well as problems with over- and under-dosing [ 50 , 54 , 60 , 74 ]. Because longitudinal on-farm surveys are time-consuming and require considerable farmer commitment, they may be affected by a low response rate, limiting their representativeness [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial use in pigs has been under the spotlight with the formation of working groups and research initiatives striving to address this high use and to promote responsible practices (8–10). Practices commonly employed in the pig sector such as the use of antimicrobials for disease prophylaxis and the commonality of the administration of in-feed antimicrobials (1113) have been associated with high and indiscriminate antimicrobial use (4, 14). These behaviors coupled with the relatively high sales of antimicrobial products, authorized for use solely in pigs, have highlighted pigs as a priority species in the UK and Europe for gaining a better understanding of prescribing and use (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Colistin causes the replacement of divalent cations (Ca +2 , Mg +2 ) in the membrane and subsequently kills the bacteria . World Health Organization has classified some kinds of antibiotic as critically important antimicrobials, including third‐generation and fourth‐generation cephalosporins, fluoroquinolones, macrolides, and recently colistin …”
Section: Introductionmentioning
confidence: 99%